Synthesis of nonionic-anionic colloidal systems based on alkaline and ammonium β-nonylphenol polyethyleneoxy (n = 3-20) propionates/dodecylbenzenesulfonates with prospects for food hygiene - Jianu Calin (Chemistry Central Journal, 2012)
Abstract Background The main objective of this work was to obtain a binary system of surface-active components (nonionic soap – alkaline and/or ammonium dodecylbenzenesulfonate) with potential competences in food hygiene, by accessing a scheme of classical reactions (cyanoethylation, total acid hydrolysis and stoichiometric neutralization with inorganic alkaline and/or organic ammonium bases) adapted to heterogeneously polyethoxylated nonylphenols (n = 3-20). In the processing system mentioned, dodecylbenzenesulfonic acid, initially the acid catalyst for the exhaustive hydrolysis of β-nonylphenolpolyethyleneoxy (n = 3-20) propionitriles, becomes together with the nonionic soap formed the second surface-active component of the binary system. Results In the reaction scheme adopted the influence of the main operating (duration, temperature, molar ratio of reagents) and structural parameters (degree of oligomerization of the polyoxyethylene chain) on the processing yields for the synthetic steps was followed. The favorable role of the polyoxyethylene chain size is remarked, through its specific conformation and its alkaline cations sequestration competences on the yields of cyanoethylation, but also the beneficial influence of phase-transfer catalysts in the total acid hydrolysis step. The chemical stability of dodecylbenzenesulfonic acid (DBSH) at the temperature and strongly acidic pH of the reaction environment is confirmed. The controlled change of the amount of DBSH in the final binary system will later confer it potential colloidal competences in food hygiene receipts. Conclusions The preliminary synthetic tests performed confirmed the prospect of obtaining a broad range of useful colloidal competences in various food hygiene scenarios.